Business Cycles, Credit Cycles and Bank Holdings of Sovereign Bonds: Historical Evidence for Italy 1861-2013 - Silvana Bartoletto; Bruno Chiarini; Elisabetta Marzano; Paolo Piselli (Center for Economic Studies and ifo Institute (CESifo), 2015)
We propose a joint dating of the Italian business and credit cycle on a historical horizon, by applying a local turning-point dating algorithm to the level of the variables. Along with short cycles, corresponding to traditional business cycle fluctuations, we also investigate medium cycles, because there is evidence that financial booms and busts are longer and persistent than the business cycle. After comparing our cycles with the prominent qualitative features of the Italian economy, we carry out some statistical tests for comovement between credit and business cycle and we propose a measure of asymmetry of this comovement, which proves to be weaker in recessions. We find evidence that credit and business cycle are poorly synchronized especially in the medium term, although, when credit and real contractions overlap, recessions are definitely more severe. We do not find evidence that credit leads the business cycle, both in the medium or in the short fluctuations. On the contrary, in the short cycle, we find some evidence that business cycle leads the credit one. Finally, credit and business cycle comovement increases when credit embodies public bonds held by banks, a bank financing to the public sector. However, in the post-WWII era, this financial backup to the public side of the economy has occurred at the expense of bank lending.
Keywords: N13; N14; 330; financial cycle; bank credit; medium-term fluctuations